Analysis of Factors Influencing The Students’ Difficulties in Achieving High Intermediate Score on Toefl ITP of English Department at Madako University - Iluh Sunari; Hidayati; Jaya (Universitas Insan Budi Utomo, 2024)
The purpose of this study is to identify the factors influencing the students' difficulties in achieving high intermediate score on the toefl itp of English Department at Madako University.The participants in this study are eight semester English students who have taken the TOEFL test and the researcher only took 8 student out of 28 over all. This study use an interview as the instrument in collecting the data and descriptive qualitative is the method of this research .Analyze and interpret the data through qualitative procedures by doing an interview, if the answer questioned after the analysis feel unsatisfactory, the researcher will ask question again until a certain point in time there is data that is considered credible. After all the data is collected, then data reduction is carried out after sorting and selecting the data essentials are completed, then the data is presented in the form of descriptive text and then conclusions are made. The finding of this study are the lack of consistent and comprehensive practice, along with low intrinsic motivation, serves as significant barriers, as many students only start practicing close to the exam and do so merely to fulfill administrative requirements. Additionally, limitations in basic English skills, particularly in grammar and listening, also affect their performance and causing the student difficult to accomplish a high intermediate score